PENGARUH PENGETAHUAN AUDITING, SKEPTISISME PROFESIONAL, DAN ETIKA TERHADAP PERSEPSI MAHASISWA AKUNTANSI UNIVERSITAS WIJAYA KUSUMA TENTANG KUALITAS AUDIT - Eunike Agrestin Ade Purnomo; Risa Watti (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aimed to determine the influence of auditing knowledge, professional skepticism, and ethics on accounting students’ perceptions of audit quality. This quantitative study used a purposive sample of 135 undergraduate students in the Accounting Program at Wijaya Kusuma University, Surabaya. Data were collected with a questionnaire, and analysis was conducted with SPSS using multiple linear regression. The results showed that auditing knowledge, professional skepticism, and ethics partially had a positive and significant influence on accounting students’ perceptions of audit quality. Furthermore, all three variables simultaneously significantly influenced students’ perceptions of audit quality. This demonstrates that the better the students’ auditing knowledge, professional skepticism, and ethics, the better their perceptions of audit quality.